"Doing hope" as a possible way towards a responsive occupational science. Issue 1 (2nd January 2021) - Mondaca, Margarita
ABSTRACT: Europe is facing many major and rapid changes, which have direct consequences for the everyday lives of people experiencing diverse situations of vulnerability. Changes in health care systems, migration, and a growing population of elderly people are just a few examples of these changes in Europe. New ways of living and the struggles associated with them, urge our community to seek sustainable ways towards social justice. I choose to speak from my position as a hybrid scholar (from the in between); formed and trained within diverse epistemologies to reflect on these issues. I aim to open a dialogue about possibilities and responsibilities to become responsive to persons and groups, where failing infrastructures in our communities expose forms of vulnerability. What can occupational science do regarding populations whose vulnerabilities are exposed? What kind of science is needed to meet these challenges? To reflect on this, I will draw on my research experiences of engaging in community building and my teaching experiences preparing future occupational therapists to face these emerging topics. I introduce the concept of 'third space' as a possible way for knowledge creation embracing democratic collaboration, negotiation, and contestation in research and learning contexts. I will conclude by engaging in a critical reflection about the epistemic privilege where occupational science is founded, and the urgency to explore and create other frames of collaboration and dialogues that allow us to construct a more just world together.